Atopic Dermatitis: A Case Study of Therapy for a Difficultly Curable Condition - Joseph Bagiwish (Newinera Publisher, 2020)
This study reviews the use of therapy for a difficultly curable condition in patient. A similar rash came back at age 12, was diagnosed as atopic eczema, and has not disappeared. Erupted, crusty, erythematous, eczematous, lichenified, maculopapular, and smooth vesicular eruptions are present on the face, neck, flexor aspects of both arms and legs, hands, and chest. It is believed that topical corticosteroids penetrate into the stratum corneum by passive diffusion, which varies greatly, depending on the part of the body on which the preparation is used. Allergic sensitization can occur within 2 weeks of therapy, but it may be difficult to diagnose because corticosteroids can modify allergic reactions.